Amber & Clay - Schlitz, Laura Amy (Candlewick Press, 2022)
Set in ancient Greece, Melisto, the privileged ten-year-old daughter of a noble, leaves her home to serve the goddess Artemis and dies in a lightning storm. Melisto then travels in spirit to reunite with her spiritual brother, Rhaskos who was separated from her at birth, lives the life of a slave, and pursues art with his master and philosophy as a student of Socrates.